Analisis Kandungan Lemak pada Asi Eksklusif dan Hubungannya dengan Pertumbuhan Tubuh Bayi - Ainun Nisa; Nurul Hekmah (HB PRESS, 2022)
Breast milk is the best source of nutrients for infants. Its content was strongly influenced by the intake of the nutrients consumed by the mother. When the mother’s nutrient intake is fulfilled, the quality of her breast milk will be good. This study aimed to analyze the nutritional intake of breast milk and the fat content in breast milk, and the association between the fat content and the growth of infants aged six months. This quantitative and observational study used a cross-sectional design. The population was nursing mothers with infants aged six months. The Posyandu was selected by purposive sampling, while the samples were selected by consecutive sampling. Based on the correlation test, the samples in this study were 56 people. The study was conducted in the three Puskesmas areas in Bandung. The data were analyzed using the chi-square test. The results showed that there were 37,5% nursing mothers with energy intake appropriate with RDA and the rest of them (62,5%) had energy intake below the RDA. There was an association between energy intake of nursing mothers with fat content in breast milk (p = 0,01). There is a relationship between fat content in breast milk with WAZ (p = 0.00). Fat content in breast milk had no association with HAZ (p=0,12) and WHZ (p=0,42). Low energy intake affected fat content in breast milk, which will eventually affect infant growth.